FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN LOSIO EKSTRAK METANOL ALGA HIJAU Caulerpa racemosa - Nurlina Nurlina; M Ilham Tomagola; Riskawati Angraini (Fakultas Farmasi UMI, 2018)
Caulerpa racemosa is one type of green algae has the ability to defend against radiation of ultraviolet. Lotion is a liquid or semi-liquid preparation containing one or more active ingredients with a suitable vehicle and provides a comfortable and good feel to the skin. The aim of this research was to obtain the optimum formula based on organoleptic testing, viscosity, pH, flow type, globule of dispersion, and antioxidant activity. The method of this research is experimentally which done by making some design of lotion formulation from methanolic extract of green alga Caulerpa rasemosa. Stability of losio was evaluated include organoleptic testing, pH measurement, type of emulsion, viscosity, flow type, size and distribution of dispersion globule. Determining of effectiveness of lotion as an antioxidant by IC50 value with UV-Vis spectrophotometry method. Results of this research collected and processed statistically with the Completely Randomized Design method, then made the discussion and taken the conclusion. Based on the evaluation, it was found that Losio containing 0.75% methanolic extract of Caulerpa racemosa green algae (Formula III) had the most optimum pharmaceutical stability. And the three losio formulas containing methanol extract of Caulerpa racemosa green algae have antioxidant activity.